UNIMAPS (CIPEEX, 2024)
UNIMAPS IS A LOCATION MAPPING SOFTWARE CURRENTLY IN THE DEVELOPMENT PHASE, WITH THE AIM OF PROVIDING A PRECISE GEOGRAPHICAL AND GEOSPATIAL VISUAL REPRESENTATION OF THE UNIVERSIDADE EVANGÉLICA DE GOIS. THIS INCLUDES IDENTIFYING POINTS OF INTEREST AND LANDMARKS, BUILDINGS, ROADS, AND OTHER RELEVANT ELEMENTS. THE METHODS BEING EMPLOYED FOR THE DEVELOPMENT OF THIS SOFTWARE WILL INVOLVE CONSUMER PROFILE RESEARCH, DESIGN DEVELOPMENT PROFILING, UNDERSTANDING OF PERSONAS, DATA COLLECTION, DATA ANALYSIS AND PROCESSING, AND DATAREPRESENTATION. IT IS EXPECTED THAT UPON THE COMPLETION OF THE DEVELOPMENT OF THIS SOFTWARE, THE ACADEMIC COMMUNITY WILL BE ABLE TO NAVIGATE TO DESIRED LOCATIONS WITH GREATER EASE, PRECISE AND UP-TO-DATE REPRESENTATION OF THE DESIRED AREA, THEREBY PROVIDING SIGNIFICANT BENEFITS FOR PLANNING, MANAGEMENT, AND DEVELOPMENT OF THE MAPPED AREA. SUCCESSFUL IMPLEMENTATION REQUIRES THE APPLICATION OF ROBUST METHODOLOGIES AND EFFICIENT USE OF REMOTE SENSING TECHNOLOGIES AND MAPPING SOFTWARE.